Financial system for a multinational family in Sharia and Law - yousf faraj muhammad hadiri (Schemata: Jurnal Pasca Sarjana IAIN Mataram, 2018)
The issue of the financial system of a multinational family in shari'a and law is of great importance in the current era of the deterioration of rights in the case of family disputes, which often result in divorce. Hence, Islamic law has taken into account this subject with many rules and provisions that protect both spouses' rights and obligations. Some Arab countries have also taken this approach, but they have not been far from international laws that advocate women's freedom, as we find in Tunisian law, for example. Here we have examined this subject from a legitimate legal point to clarify the problem that some countries have occurred when they put the family laws. The family laws have come up with sub-solutions that have made them fundamental issues that would raise the status of women and strengthen their legal and social status. This is the result of satisfying the demands of a predominantly political nature of religion, which made some laws rigid. The obligation of positive laws should not be affected by the purposes of Islamic law and its lofty principles of political, because codification does not prohibit Hara’am things, and it is not Hara’am for Halaal and non-ijtihad.